Parenting Patterns For Broken Home Children - Burhanuddin, Hamam; Khumaini, Fahmi; Thohiroh, Muhaiminatut (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
The divorce rate in Bojonegoro Regency has increased. Based on data in the 2019 divorce rate reached 956 divorce cases amounted to 1915. In 2020 the divorce rate was 914 and the number of divorce lawsuit was 1979. The sub-district that experienced the highest divorce cases was the Dander District's increase in divorce cases, which will impact the parenting pattern of abandoned children.. This study aims to determine the parenting pattern of broken home children in Dander District, Bojonegoro Regency focus of this research is on the intellectual and psychological characteristics of children who experience broken home. This research is field research with a qualitative approach. The research subjects consisted of three broken-home children with different backgrounds: divorced, deceased, and parents who were not present for a long time. Data collection techniques are observation, in-depth interviews, and documentation.. Data collection techniques are observation, in-depth interviews, and documentation. Data analysis techniques are data reduction, data presentation, and verification of conclusion drawing, Validity of the findings using extended observations, researcher persistence, and triangulation. The results of this study are the parenting patterns applied to children from broken homes are democratic parenting and permissive parenting. The terms of their intellectuals are a decrease in cognitive abilities, reading delays and difficulty concentrating during the learning process, while the psychological characteristics that occur in children are that children tend to have bad temperaments, emotional instability, are sensitive and have closed personalities. Parenting consists of internal factors and external factors. Internal factors include parental attention, parental religious understanding, and parental education. While external factors include the environment where the child lives. Keywords: Parenting, Broken Home Children